PROTEIN RESIDUE (CIEP) ANALYSIS OF SAMPLES FROM SITE 118X77, NAHANNI NATIONAL PARK RESERVE, NORTHWEST TERRITORIES - Scott Cummings, Linda (PaleoResearch Institute); Clark, Caitlin A. (Paleoresearch Institute) (the Digital Archaeological Record)
Two obsidian flakes were recovered from Site 118X77, which is located in Nahanni National Park Reserve in southwest Northwest Territories, Canada. The flakes were submitted for protein residue analysis to identify possible processed animal proteins. The flakes were also submitted for obsidian sourcing to determine where the flake materials originated.